Insights into pāhoehoe lava emplacement using visible and thermal structure-from-motion photogrammetry - Biass, Sébastien (2020)
We present the evolution over 3 months of a 2016–2017 pāhoehoe flow at Kīlauea as it changed from a narrow sheet flow into a compound lava field fed by a stable system of tubes. The portion of the flow located on Kīlauea's coastal plain was characterized using helicopter-based visible and thermal structure-from-motion photogrammetry to construct a series of georeferenced digital surface models and thermal maps on eight different days. Results reveal key influences on the emplacement and evolution of such long-lived pāhoehoe flows. This region of the flow grew by ~12 × 106 m3 with a near-constant time-average discharge rate of 1.2–2.7 m3/s. The development of two tube systems is captured and shows an initial nascent tube enhanced by a narrow topographic confinement, which later inflated and created a topographic inversion that modulated the emplacement of a second flow lobe with its own tube system. The analysis of breakouts at various stages of the field's life suggests that the evolution of the thermal and morphological properties of the flow surface reflect its maturity. Thermal properties of breakouts were used to expand the empirical relationship of breakout cooling to longer timescales. This study contributes to the long-term development and validation of more accurate predictive models for pāhoehoe, required during the management of long-lasting lava flow crises in Hawai'i and elsewhere.